PENGARUH KOMITMEN ORGANISASI DAN STRES KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT. UNITED MOTORS CENTRE CABANG BASUKI RAHMAT SURABAYA - Dwi Aldila Desawa; I Made Bagus Dwiarta (Majalah Ekonomi, 2015)
The research aims to test the importance of organizational competencies in order to improve employee job satisfaction in PT. United Motors Center Branch Basuki Rahmat Surabaya. Some of the variables analyzed as factors influencing job satisfaction of organizational commitment (X_1), and work stress (X_2). This research population is 300 employees and a sample set based on quota sampling technique as much as 75 employees. The data collected through questionnaires and analyzed using the Multiple Linear Regression Statistics. Based on data analysis, it was concluded that there was a simultaneous influence of F value = value with the 21.320 sig = 0.000 (0.000 â‰¤ 0.05). Whereas the testing of partially variable indicating each effect on satisfaction with the value t = 2.417 organizational commitment with a value of 0,018 GIS., work and stress of a sign-value 4.431. The overall analysis it was concluded that work stress variables affect predominantly towards job satisfaction. On a theoretical level, the study supports the theory of organizational behavior and human resources as well as some earlier research. While on a practical level, the authorities thought contributed to better understand the importance of reducing work stress on employees in order to improve the work of employees.